Competitive Strategy and Performance in Traditional Food SMEs: The Role of Competitive Advantage - Vera Sylvia Saragi Sitio; Novita Damayanti; Yohanes Ferry Cahaya; Shirley M.C. Yeung; Sri Yanthy Yosepha (Universitas Mercu Buana, 2026)
Objective: Improving business success remains a problem for traditional food SMEs. Digital literacy, productivity, legality, financing, branding, human resources, certification products, standard distribution, quality products, quantity products, and customer services are all necessary because of the lack of innovation and technology.Methodology: This research uses a quantitative approach with Structural Equation Modelling (SEM). The statistical method used to determine the objectives of the study was SmartPLS 3.0.Data collection through a questionnaire and distributed to SMEs in Jabodetabek (Jakarta, Bogor, Bekasi, and Tangerang). The data was obtained 300 respondents.Findings: The findings demonstrated that entrepreneurial approach had little bearing on how well a business performed. Conversely, market orientation had a favourable and noteworthy impact on firm performance, entrepreneurial orientation on competitive advantage, and market orientation on competitive advantage. Business performance is influenced by competitive advantage as an intervening variable.Conclusion: These findings prove that managerial skills, decision-making, entrepreneurial orientation, and innovation are essential for traditional food SMEs to optimize business performance and achieve competitive advantage. In addition, this research provides the right insights for the government, SME players, and customers in achieving SMEs’ business goals and promoting traditional Indonesian food products in both domestic and global markets.